SIFAT FISIK TANAH DAN PERTUMBUHAN TANAMAN KARET (Hevea brasiliensis Muell. Arg) PADA BEBERAPA KONDISI PENUTUPAN LAHAN DENGAN Mucuna bracteata - Harist, Abduh; Wawan, Wawan; Wardati, Wardati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The objectives of this research was to know the physical properties of peat soil and growth of rubber plant on several ground cover condition by Mucuna bracteata at social plantation area of  PT. RAPP, Teluk Meranti Subdistrict, Pelalawan Regency, Riau Province. Soil analysis was carried out the laboratory of soil science Faculty of Agriculture, University of Riau. This research was carried out from January to March 2016 and the determination of the area of sampling arranged using purposive sampling methods thats are sampling of rubber plant contained living mucuna, passed of mucuna, and without mucuna. Variables observed in this research include of the soil physical properties and observation of rubber plant. Observation of the soil physical properties were soil colour, soil temperature, soil moisture, bulk density, soil particle density, total pore space, soil permeability, and water holding capacity. Parameter observed of rubber plant is circular stem. The result showed that peat soil covered by living mucuna have soil physical properties (soil moisture, soil temperature, and water holding capacity) higher than passed of mucuna and without mucuna. At the rubber plant covered by living mucuna also showed circular stem higher than rubber plant on the passed of mucuna but on the passed of mucuna have circular stem higher than without mucuna. Keywords : Soil physical properties, peat soil, Mucuna bracteata, rubber plant